2011
DOI: 10.4048/jbc.2011.14.1.14
|View full text |Cite
|
Sign up to set email alerts
|

αB-Crystallin is a Novel Oncoprotein Associated with Poor Prognosis in Breast Cancer

Abstract: PurposeαB-crystallin, a small heat shock protein, is an anti-apoptotic protein associated with aggressive tumor behavior. A recent study revealed that αB-crystallin is overexpressed in a metastatic variant of the GI101A human breast carcinoma cell line. The purpose of this study was to investigate whether αB-crystallin is related to other breast tumor markers and can predict a breast cancer prognosis.MethodsEighty-two patients who underwent breast cancer surgery at Hallym Sacred Heart Hospital were enrolled. α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…A promising approach in cancer therapy also might be targeting HSP, because up-regulated Hsp90 and Hsp70 in cancer cells have been recognized as important drug targets and are under intensive studies in recent years. HSP are currently being targeted in the therapy of breast cancer and other carcinomas and effective drugs for Hsp90 (e.g., geldanamycin and its analogs) have been synthesized and evaluated in clinical trials (Calderwood and Gong, 2011; Kim and Kim, 2011). HSP vaccines have been intensively studied in the preceding two decades, proving to be safe and effective in treating a number of malignancies (Murshid et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A promising approach in cancer therapy also might be targeting HSP, because up-regulated Hsp90 and Hsp70 in cancer cells have been recognized as important drug targets and are under intensive studies in recent years. HSP are currently being targeted in the therapy of breast cancer and other carcinomas and effective drugs for Hsp90 (e.g., geldanamycin and its analogs) have been synthesized and evaluated in clinical trials (Calderwood and Gong, 2011; Kim and Kim, 2011). HSP vaccines have been intensively studied in the preceding two decades, proving to be safe and effective in treating a number of malignancies (Murshid et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that αB-crystallin is expressed in about half of basal-like breast tumors and promotes an invasive, apoptosis-resistant phenotype in breast epithelial cells [18]. Others have confirmed the association of αB-crystallin expression with poor outcomes and the basal-like/triple-negative subtype of breast cancer and described a similar oncogenic role for αB-crystallin in the pathogenesis of glioblastoma multiforme [16, 35, 36]. It is tempting to speculate that the observed role of αB-crystallin in suppressing caspase activation in setting of Rb inactivation and p53 inhibition might account for the frequent occurrence of these three molecular events ( Rb loss, TP53 mutation, and αB-crystallin expression) in clinically aggressive triple-negative breast cancers, although it remains to be determined how frequently all three of these events occur in individual basal-like/triple-negative tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have confirmed the association of αB-crystallin protein expression with expression of basal markers ( e.g. , cytokeratin 5 and 14) and TNBC, which is associated with poor survival due to early relapse in the lungs and brain (Moyano et al, 2006; Ivanov et al, 2008; Smid et al, 2008; Kennecke et al, 2010; Kim et al, 2011; Toft & Cryns, 2011; Tsang et al, 2012; Malin et al, 2014). αB-crystallin is also commonly expressed in metaplastic carcinomas, a rare histologic subtype with spindle or sarcomatoid features that express basal markers and are likely to represent a distinctive subset of basal-like breast tumors (Reis-Filho et al, 2006; Sitterding et al, 2008; Chan et al, 2011).…”
Section: Deregulated Expression In Cancermentioning
confidence: 95%
“…αB-crystallin is abundantly expressed in a multitude of solid tumors, including malignant glioblastomas, osteosarcoma, retinoblastoma and carcinomas of the breast, prostate, ovary, colon, liver, lung (non-small cell), head and neck, and thyroid (Aoyama et al, 1993; Wulfkuhle et al, 2002; Stronach et al, 2003; Chelouche-Lev et al, 2004; Shi et al, 2004, 2014; Chin et al, 2005; Moyano et al, 2006; Goplen et al, 2010; Kim et al, 2011; Mao et al, 2012; Huang et al, 2013; Volkmann et al, 2013; Davidov et al, 2014; Qin et al, 2014; Yilmaz et al, 2015). In many cases, αB-crystallin levels are higher in the tumor tissue than the surrounding non-tumor tissue (Wulfkuhle et al, 2002; Shi et al, 2004, 2014; Mao et al, 2012; Qin et al, 2014; Yilmaz et al, 2015).…”
Section: Deregulated Expression In Cancermentioning
confidence: 99%